ANALISIS SPASIAL ZONA POTENSI RAWAN LONGSOR DISEKITAR RUAS JALAN RAYA MATARAM-TANJUNG - Adi, Wiwit Bayu; Anshar, Aliful; Muladi, Agum; Wahyudi, Try; Harmaen, Harmaen (Universitas Muhammadiyah Gorontalo, 2024)
This research aims to analyze the spatial distribution of landslide prone zones around Mataram-Tanjung highway. The second objective is to determine whether the utilization of GIS can be used properly to analyze the potential prone to landslides in an area based on several indicators used. The method used is overlay analysis and utilizing Geographic Information System (GIS) application. The variables used are soil type, rainfall, slope, geological type and land cover type. The result of the analysis shows that the distribution of landslide prone potential zone in the study area has 4 classes, namely very low landslide prone potential class, low prone potential, medium prone potential and high prone potential. The application of sapsial analysis by utilizing GIS can help in predicting an area that is potentially prone to landslides, this is reinforced by the results of field validation where the results of the analysis have been appropriate to describe the existing conditions.